PAX2 Expression in Endometrial Intraepithelial Neoplasia - Zahra Abbas Fadhil; Sazan Abdulwahab Mirza; Sahira Abood Ali (Indian Journal of Forensic Medicine & Toxicology, 2021)
Endometrial intraepithelial neoplasia (EIN) is a clonal growth of glands of the endometrium, regardedas a precancerous condition because of its highcorrelation with endometrioid adenocarcinoma of theendometrium of uterus.Objective: To evaluate the expression of PAX2 in EIN and to correlate the expression with clinicalparameters.Materials and Methods: - This is a retrospective study for (57)totalcasesof D&C and endometrial pipplebiopsies, (21) cases where diagnosed as hormonal imbalance, (26) cases where diagnosed as EIN and (10)cases where diagnosed as endometrioid endometrial adenocarcinoma.Results: -Total number of cases that showed completely loss of PAX2 expression in all this study groups25/57 and cases that showed partial loss 10/57. In hormonal imbalance group: all the cases showed normalexpression of PAX2. In EIN: (65.4%) of cases were with complete loss of PAX2, (30.4%) with partial loss.In endometrial endometrioid cancer group:80% of cases with complete PAX2 expression, while partialloss or decrease PAX2 expression did occur in only (20%) ofcases.The association between study groupsand PAX2 expression:decrease and complete loss of PAX2 staining were significantly (P= 0.001) occurredin cases of EIN and endometrial endometroid adenocarcinoma, while there was insignificant association(P=0.635) between study groups (EIN and endometrial endometroid adenocarcinoma), and results of PAX2expression.Conclusion: -Loss of PAX2 immunomarkerexpressionhappens early and during of EIN using the WHOdiagnostic categories.